Clear, consistent and engaging (European Central Bank, 2021)
This paper examines the importance of central bank communication in ensuring the effectiveness of monetary policy and in underpinning the credibility, accountability and legitimacy of independent central banks. It documents how communication has become a monetary policy tool in itself; one example of this being forward guidance, given its impact on inflation expectations, economic behaviour and inflation. The paper explains why and how consistent, clear and effective communication to expert and non-expert audiences is essential in an environment of an ever-increasing need by central banks to reach these audiences. Central banks must also meet the demand for more understandable information about policies and tools, while at the same time overcoming the challenge posed by the wider public’s rational inattention. Since the European Central Bank was established, the communications landscape has changed dramatically and continues to evolve. This paper outlines how better communication, including greater engagement with the wider public, could help boost people’s understanding of and trust in the Eurosystem.
10.2866/792805
Keywords: Graue Literatur; central bank; forward guidance; transparency; accountability; trust